Lidar Network for Temperature and Wind Measurements in the Mesosphere and Lower Thermosphere Region - Y. Yang; F. Li; X. Cheng; G. Yang; D. Lyu; X. Lin; L. Liu; X. Fang; J. Zheng; L. Du; W. Wang; L. Ren; et al. (Space Weather)
Abstract A sodium lidar (light detection and range) network for the Earth's mesosphere and lower thermosphere (MLT) temperature, wind and sodium density measurements is designed and constructed in the second phase of the Chinese Meridional Project. Five narrowband sodium lidar systems are deployed across various regions in China, designed and developed based on similar principles and structures. They adhere to uniform data processing standards and operate under the same observational protocols. This allows them to form a network of lidar systems capable of detecting temperature and wind fields in the MLT. The preliminary observation results of the lidar near Tibetan plateau is demonstrated in this paper. This lidar network offers horizontal perspectives on large scale that a single‐station lidar system can't provide. Its future observations are expected to advance the understanding of atmospheric waves by studying wave propagation, chemical‐dynamical coupling processes and the horizonal structure of in the MLT region.